Tumor Necrosis Factor Alpha Inhibition for Inflammatory Bowel Disease after Liver Transplant for Primary Sclerosing Cholangitis. (15th May 2018) - Parekh, Ravish; Abdulhamid, Ahmed; Trudeau, Sheri; Kaur, Nirmal
Abstract : Background. Outcome data regarding the use of tumor necrosis factor alpha inhibitors (anti-TNF α ) in patients with inflammatory bowel disease (IBD) after liver transplant (LT) for primary sclerosing cholangitis (PSC) are scant. Methods. We performed a retrospective chart review to investigate outcomes among a series of post-liver-transplant PSC/IBD patients receiving anti-TNF α therapy at Henry Ford Health System ((HFHS), Detroit, MI). Results. A total of five patients were treated with anti-TNF α agents for IBD after LT for PSC from 1993 through 2015. Two patients were treated with adalimumab, and three were treated with infliximab. Three patients were hospitalized with severe posttransplant infections. Two patients developed posttransplant lymphoproliferative disease (PTLD); one of these patients died due to complications of PTLD. Conclusion. Anti-TNF α treatment following LT worsened the disease course in our patients with concurrent PSC/IBD and led to serious complications and surgical intervention. Larger studies are needed to evaluate the side effects and outcomes of the use of such agents in this patient population. Until then, clinicians should have a high threshold to use anti-TNF α therapy in this setting.